Study of The Phonological and Structural Aspects of American Dialects - Kazakova, Marifat; Abduhamidova, Shohista (Indonesian Journal Publisher, 2025)
This study investigates the phonological and structural characteristics of American English dialects, with a focus on regional variations such as Southern English, African American Vernacular English (AAVE), and the Northern Cities Shift. The research aims to analyze how historical, social, and cultural factors influence dialectal differences. Using linguistic analysis and comparative studies, the findings reveal significant shifts in vowel pronunciation, consonant usage, and syntactic structures. The study contributes to understanding dialect evolution and its impact on identity and communication.